Peran Media Digital terhadap Komunikasi Perusahaan (Literature Review) - Siringo Ringo, Lewis Hamonangan; Febrina, Maria; Khaerunnisah, Amaliah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of digital media in corporate communication. In the digital era, companies increasingly rely on various digital platforms to enhance the effectiveness of both internal and external communication. Digital media enables companies to build their image, expand audience reach, and increase engagement with customers and other stakeholders. Therefore, this study explores how digital media contributes to corporate communication strategies and its impact on organizational communication effectiveness.The research method used in this study is a literature review, collecting and analyzing various journals, books, and scholarly articles related to corporate communication in a digital context. The reviewed sources include previous studies discussing the role of social media, websites, email, and other digital platforms in supporting corporate communication. The analysis focuses on trends, challenges, and opportunities presented by digital media for companies in communicating with their audiences.The findings indicate that digital media plays a significant role in enhancing corporate communication by reaching a broader audience, enabling faster interactions, and fostering greater engagement. The use of digital media has been proven to strengthen corporate branding, improve transparency, and facilitate more effective two-way communication with customers and business partners. However, challenges such as digital crisis management, data security, and information overload remain critical concerns that must be addressed to ensure optimal corporate communication in the digital era.